2016
DOI: 10.1515/bejeap-2015-0202
|View full text |Cite
|
Sign up to set email alerts
|

Profit Improving via Strategic Technology Sharing

Abstract: This paper investigates whether a downstream monopolist has an incentive to freely share its technology to potential entrants. With a linear demand, it is more profitable for the downstream monopolist to share its obsolete technology with the potential entrants even with no returns. In this context, technology sharing is a Pareto improvement. Moreover, the profit of the downstream monopolist via technology sharing increases with the number of new entrants, but the nexus between social welfare and the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Levy (2012) revealed that technology sharing could accelerate the development of process innovation, thereby boosting firms' profit and innovation. Kao and Peng (2016) addressed the scenario where a downstream firm decided whether to share its technology when facing competitors lacking core technologies. Sharing technology with these competitors could reduce the upstream firm's wholesaling price, and their results showed that the downstream firm would benefit more from the technology sharing behavior despite the rise of market competition.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Levy (2012) revealed that technology sharing could accelerate the development of process innovation, thereby boosting firms' profit and innovation. Kao and Peng (2016) addressed the scenario where a downstream firm decided whether to share its technology when facing competitors lacking core technologies. Sharing technology with these competitors could reduce the upstream firm's wholesaling price, and their results showed that the downstream firm would benefit more from the technology sharing behavior despite the rise of market competition.…”
Section: Related Literaturementioning
confidence: 99%
“…Specifically, Manufacturer 1's fixed cost is categorized as a sunk cost, while Manufacturer 2 is assumed to incur a fixed cost f > 0 for the development of the innovative products as it invests in physical assets and human resources to initiate the production. For the variable cost associated with, say, the raw materials for each product, we assume that the two manufacturers incur a cost of c (c > 0) per unit product in the innovation (Kao & Peng, 2016;…”
Section: Model C: Non-zero Innovation Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the firms, Cao and Song (2021) discussed the effects of manufacturers' technology sharing on suppliers' technology investment decisions. Kao and Peng (2016) examined whether downstream monopolists have an incentive to share their technologies with potential entrants. The results indicated that, under linear demand, it is beneficial to share outdated technologies with potential entrants, even if there is no return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technology sharing is an important dimension of firm sharing. Research on technology sharing mainly focuses on its influence and the factors affecting sharing agreements between firms.Research on the influence of technology sharing mainly includes the internal influence on the firm and external influence outside the firm.Regarding the firms,Cao and Song (2021) discussed the effects of manufacturers' technology sharing on suppliers' technology investment decisions Kao and Peng (2016). examined whether downstream monopolists have an incentive to share their technologies with potential entrants.…”
mentioning
confidence: 99%